The Role of Malcolm X's Speeches in Solidifying his Autobiography (Universitas Negeri Semarang, 2020)
This paper demonstrates how a literary text can be approached through a linguistic framework to enhance one’s reading and interpretation of it. It aims at examining the power of The Autobiography of Malcolm X: As Told to Alex Haley by analyzing the narrator’s description of his early speeches. I draw upon the appraisal framework, and I focus on Malcolm’s utilization of affect, judgment, and appreciation in a number of his speeches that he reported in the book. In those speeches, Malcolm adopts resources from the appraisal framework to align his audience with his position. His performance of affective stance to construct the entire problem of race in America contributed to the success of his book for more than 50 years since its publication.